Designing transdisciplinarity for transformative ocean governance - Hills, Jeremy Maxwell; Maharaj, Payal Nandini (Frontiers in Marine Science, 2023)
The 2030 Agenda for Sustainable Development sets out a transformative vision which has yet to be realised for SDG14 and oceans. Recognition of the “indivisibility” of the Goals and enhanced integration of ocean governance support this transformation, but require at least multidisciplinary, or probably transdisciplinary, approaches. For regions which are highly dependent on development finance, a powerful leverage point for a transdisciplinary transformation is in the design of development investments. The work presented here identifies design features of ocean development-financed projects involving substantial amounts of research in two Pacific Small Island Developing States (SIDS): Fiji and the Solomon Islands. Transdisciplinary approaches were closely aligned to what is established as Mode 2 research modalities which focus on participation and multi-knowledge systems, as opposed to Mode 1 which have a predominantly scientific basis. From the literature an analytical indicator framework was developed which scored projects on their Modes of research within four categories: Product, Process, Policy and People. This framework was applied to five development-financed projects, and permitted the balance of Mode 1 and Mode 2 to be assessed and significant differences between projects identified. The work surfaces project features which can be embedded in the design of ocean investments which promote transdisciplinarity. This tractable and practical recognition of transdisciplinarity has connotations to the UN Ocean Decade in its ability to deliver on its transformation rhetoric. With capacity weaknesses and constrained financial resources in developing countries, and urgent ocean-related challenges especially in SIDS, moving to designed-in transdisciplinary and transformational outcomes remains a priority.